Vocational Guidance as a Tool Against the Abandonment of the University - PaÃ§ukaj, Sokol (Mediterranean Journal of Social Sciences, 2010)
One of the most important choices of students in their lives is undoubtedly the choice of the university they want to attend. The orientation of young people is a strategic resource which is expressed in many activities that in turn aims at training and enhancing the ability of students to know themselves, the living environment, socio-economic and cultural changes, deals training, being protagonists of a personal life project and participate in the study, family and social life in an active, equal and responsible way. Improper orientation brings with it serious consequences for those who have less support, especially in cases of expulsion from educational system. In their choice of university courses is good to avoid referring only to return to school or especially concentrating on grades in academic subjects. It should expand the vision to discover the tendencies and the vocation of the person, and then his/her desire to face challenges ahead.